PERANAN CORPORATE STRATEGY DALAM KESUKSESAN-KEGAGALAN MERGER & AKUISISI: SUATU TELAAH LITERATUR - Lako, Andreas (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2004)
Most empirical studies and literature reviews documented that the final results of the wave of mergers and acquisitions in the United States, Canada, and European countries during the decade of 1980s, 1990s and 2000s were always dissatisfactory. In fact, the extent of the failure is higher than the success.However, a comprehensive investigation on the factors motivating the rise of mergers and acquisitions and the causes for success and failure is still rare. This paper reviews the contribution of corporate strategy in success and failure of mergers and acquisitions during three decades. Specifically, this paper reviews literatures with respect to the motives of corporate mergers and acquisitions actions and the trigger factors of their failures. The result of the literature review shows that corporate strategy has a significant contribution to the extent of the success and failure of corporate mergers and acquisitions. The review finds that trigger factors of mergers and acquisitions failure are the ambiguous communications and cross-cultural gaps, inappropriate and insufficient integration and transformation of new corporate culture, incompatible leadership style accustomed with a new corporate climate, inappropriate corporate planning and internal consolidation, inappropriate anatomy of organizational internal factors, and erroneousness in choosing the partners and the timing of mergers and acquisitions. To ensure the successful and sustainability of corporatemergers and acquisitions, therefore, top management and task force of mergers and acquisitions need to accurately consider those internal and external organization factors.Keywords: merger and acquisition, corporate strategy, cross-cultural, financing and operatingsinergy, stockholder wealth.